Semitic Text Thresholds in the Monetary Achievement of Professor Dr. Faziz Taha Omar Study in Light of the Criticism of Literary Criticism - Mezban, Zahraa Mohammed; Hussein, Zainab Abdul Ameer (Journal of Ecohumanism, 2024)
The research aims to identify the most important text thresholds found in the monetary achievement at Prof. Dr. Faziz Taha Omar and study them in detail with an indication of the reasons for their formulation as such. They were employed on two indicative and another synthetic levels, starting with the title threshold that is the first threshold of each literary text and then the cover threshold that serves as a visual input to the subject of the text, Followed by the gifting threshold which serves as a parallel text to the original text and is no less important than the rest of the thresholds, The search concludes with the threshold of the introduction representing the input and the initiation before the basic text.